Self-medication among Undergraduate Medical Students of Alexandria Faculty of Medicine: Where do We Stand? - Marwa Ramadan; Asmaa Eltaweel; Tamwe El Nakhal; Hanan Hemead; Abdelrahman Maraqa; Doha Abish; Rana Essam; Azza Baraka (University Library System, University of Pittsburgh, 2018)
Background: The aim of the present study was to assess the prevalence of self-medication among undergraduate medical students in Alexandria Faculty of Medicine and recognize the patterns and the attitude of students towards intake. Methods: A cross-sectional study was conducted among undergraduate medical students attending Alexandria Faculty of Medicine from both national and international programs during the period of June 2013 until October 2013. A self-administrated, semi-constructed questionnaire was used to assess the practice of self-medication among 408 students who were randomly selected using a stratified random sample technique. Results: Self-medication was reported by 208 (52.7%) students, with no significant difference between males and females. The highest percentage of self-medication was reported among those who have completed six years of academic study and the lowest was reported among those who have completed two years of academic study. There was a statistically significant association between educational stage (preclinical and clinical) practice of self-medication. Most common medications involved were analgesic and anti-inflammatory followed by decongestants, antimicrobials and antihistaminic drugs. 309 (78.8%) students believed that self-medication is acceptable. Conclusion: The present study demonstrated that self-medication is practiced by more than half of undergraduate medical students in the Faculty of Medicine - Alexandria University. Acquiring medical knowledge seems to be associated with the practice of self-medication. Therefore, more attention should be paid to medical curricula to raise awareness and limit the hazardous effects of this phenomenon